Hybrid transgastric appendectomy is feasible but does not offer advantages compared with laparoscopic appendectomy: results from the transgastric appendectomy study - Schoenberg, Markus B.; Magdeburg, Richard; Kienle, Peter; Post, Stefan; Kähler, Georg (Surgery, 2017)
Background: Very few transgastric procedures, the original objective of natural orifice translumenal surgery, have been reported in the international Natural Orifice Translumenal Surgery registers. In addition, most cases were controlled mainly by laparoscopy. To show the feasibility of hybrid transgastric appendectomy and to compare results with laparoscopic a prospective, nonrandomized study was conducted. Methods: From October 2010 to May 2013, patients with acute appendicitis were screened. If the patients met the inclusion criteria, transgastric appendectomy was offered. If the patient decided on laparoscopy, the consenting patients took part in the observational part of the study. The transgastric appendectomy procedure was controlled completely by the gastroscope, although a 3 mm grasper was used to tauten the appendix. Demographic and clinical parameters were collected. Quality of life and pain were measured with a Short Form-8 questionnaire and the Visual Analogue Scale. Results: Of the 273 patients who underwent an appendectomy, 65 agreed to take part in this study. Out of these, 30 (46.15%) underwent transgastric appendectomy and 35 (53.85%) underwent laparoscopy. No intraoperative complications were recorded. The operation duration rate was greater in the transgastric appendectomy group (94.5 minutes vs 69 minutes; P < .001). Conversions to open appendectomy and complications were the same. There were no differences in pain preoperatively or postoperatively. In both the transgastric appendectomy and laparoscopic groups, the quality of life of all the subscales increased markedly after successful resection of the pathology. Conclusion: These preliminary results demonstrate the feasibility of transgastric appendectomy. The postoperative course and quality of life are comparable with laparoscopic appendectomy, but no improvement due to transgastric appendectomy could be demonstrated.
Available online 23 April 2017
Gesehen am 13.07.2018